Changed salt appetite and central angiotensin II-induced cellular activation in rat offspring following hypoxia during fetal stages - Yang, Weili (2010)
Hypoxia in pregnancy may induce fetal growth restriction and cause functional abnormalities during development. The present study determined the long-term influence of hypoxia in fetal life on dipsogenic behavior linked to central angiotensin (Ang) network in the offspring rats. Fetal blood pO(2) and body weight were decreased by hypoxia during pregnancy, followed by a postnatal “catch-up” growth. Subcutaneous hypertonic saline or intracerebroventricular Ang II significantly increased salt intake in the offspring prenatally exposed to hypoxia, while water intake was the same between the two groups. Ang II-induced c-fos expression was detected in the paraventricular nuclei, median preoptic nuclei, supraoptic nuclei, and subfornical organ in the brain, in association with reduced forebrain AT(2) receptor protein abundance in the offspring prenatally exposed to hypoxia. Levels of central AT(1) receptor protein were not changed between the two groups. Hypoxia during pregnancy could be linked to developmental problems related to behavioral dysfunctions in body fluid regulations in later life, in association with the change in central angiotensin II-mediated neural activation and expression of the Ang II receptor in the brain.